Village Development Policy Program Implementation Buton Regency - Hasni, Hasni; Sujana, I Wayan (Institute for Research and Community Service, 2022)
This study aims to determine the implementation of the village fund policy in the Matanauwe village development program, Siotapina sub-district, Buton district. The research method used is qualitative, where the research method is based on the philosophy of post-positivism and is used to study the state of natural objects rather than experiments. The researcher is a key tool, the data collection method is triangulation, the data analysis is inductive/qualitative, and the results of qualitative research focus more on meaning than generalization. The sample of this study is a component of the total number and characteristics of the overall population of the Matanauwe Village Policy Foundation, Siotapiana District, Buton Regency. The data sources used are primary data sources and secondary data sources. While the data collection methods used are observation, interviews and documentation. The result of the research is that the management of the village fund budget in Matanauwe village is well implemented. Management of the village fund budget includes: Organizing PAUD/TK/TKA/TPQ/Madrasa Non-Formal Owned by the Village (Honor Clothing etc.), Organizing posyandu (supplementary food, Pregnant class, Lamsia), Organizing village health alerts, procuring street lights and emergency handlers.